Effects Of Neuroscience-Based Thinking (NBT) And Thinking Skills (TS) Strategies On Thinking And Emotion Among Primary Schools Pupils - Ali Salim Rashid, Al-Ghafri (2011)
The aim of this study is to investigate the effects of Neuroscience-Based Thinking (NBT) strategy and Thinking Skills (TS) strategy on creative thinking and the performance of science tasks (thinking and emotion) among Malaysian pupils in primary schools. This study used quasi-experimental research design with one control group and two experimental groups. Ninety eight pupils enrolled in standard five during the 2010 educational year formed the sample. The two experimental groups were named NBT and TS while prevalent strategy (P) as the control group.